THE TRANSFORMATION OF THE BEUT DARÔH AND KENDURI KHATAM TRADITIONS IN URBAN COMMUNITY OF BANDA ACEH CITY - Al-Fairusy, Muhajir; Ikhwan, M.; Aziz, Darlis; Mulia, Muji (AKADEMIKA: Jurnal Pemikiran Islam, 2022)
This study aimed to investigate the issue of religious traditions in Aceh from the perspective of understanding and interpreting Quran, specifically focusing on the beut darôh tradition, culminating in the ceremony of kenduri khatam. This indigenous ritual has been practiced for a long time in Aceh culture and is exclusively celebrated during the month of Ramadan. Moreover, the main objective of the beut darôh is to enliven the night during Ramadan after the tarawih prayer in every mosque and meunasah (Muslim house of worship), often in rural communities. This ritual reaches its peak at the end of Ramadan with the commemoration of kenduri khatam, an inclusive ritual engaging the entire community. Specifically, Aceh Besar and Banda Aceh were the primary areas where this practice evolved and changed. This study commenced with the question, "Why have the beut darôh and kenduri khatam traditions developed in Aceh urban community?", adopting qualitative method and incorporating grounded study. The results showed that the beut darôh and kenduri khatam traditions were integral parts of Aceh religious identity and culture. The beut darôh was not merely a custom of collective Quran reading but also an educational space for Quran learning. Aceh community considered kenduri khatam as an expression of gratitude, comprising both social interactions and religious customs in local traditions. In addition, the beut darôh tradition was initially prevalent in Aceh rural communities, and gradually expanded in urban communities, even though there were practical distinctions in this tradition.